Four‐Spacecraft Magnetic Curvature and Vorticity Analyses on Kelvin‐Helmholtz Waves in MHD Simulations. Issue 1 (26th January 2018) - Kieokaew, Rungployphan; Foullon, Claire; Lavraud, Benoit
Abstract: Four‐spacecraft missions are probing the Earth's magnetospheric environment with high potential for revealing spatial and temporal scales of a variety of in situ phenomena. The techniques allowed by these four spacecraft include the calculation of vorticity and the magnetic curvature analysis (MCA), both of which have been used in the study of various plasma structures. Motivated by curved magnetic field and vortical structures induced by Kelvin‐ Helmholtz (KH) waves, we investigate the robustness of the MCA and vorticity techniques when increasing (regular) tetrahedron sizes, to interpret real data. Here for the first time, we test both techniques on a 2.5‐D MHD simulation of KH waves at the magnetopause. We investigate, in particular, the curvature and flow vorticity across KH vortices and produce time series for static spacecraft in the boundary layers. The combined results of magnetic curvature and vorticity further help us to understand the development of KH waves. In particular, first, in the trailing edge, the magnetic curvature across the magnetopause points in opposite directions, in the wave propagation direction on the magnetosheath side and against it on the magnetospheric side. Second, the existence of a "turnover layer" in the magnetospheric side, defined by negative vorticity for the duskside magnetopause, which persists in the saturation phase, is reminiscent of roll‐up history. We found significant variations in the MCA measures depending on the size of the tetrahedron. This study lends support for cross‐scale observations to better understand the nature of curvature and its role in plasma phenomena. Key Points: Varying tetrahedron sizes are used to study magnetic curvature and vorticity analyses in a MHD simulation of KH waves at the magnetopause In the trailing edge of the KH wave, the magnetic curvature across the magnetopause points in opposite directions The development of negative vorticity on the dusk magnetospheric side is contrary to expected and persists in the saturation phase